Role of the Contra-Lesional Corticoreticular Tract in Motor Recovery of the Paretic Leg in Stroke: A Mini-Narrative Review - Jang, Sung Ho; Cho, Min Jye (Frontiers in Human Neuroscience, 2022)
This review discusses the role of the contra-lesional corticoreticular tract (CRT) in motor recovery of the paretic leg in stroke patients by reviewing related diffusion tensor tractography studies. These studies suggest that the contra-lesional CRT can contribute to the motor recovery of the paretic leg in stroke patients, particularly in patients with complete injuries of the ipsilesional corticospinal tract and CRT. Furthermore, a review study reported that the motor recovery of the paretic ankle dorsiflexor, which is mandatory for achieving a good gait pattern without braces in hemiparetic stroke patients, was closely related to the contra-lesional CRT. These results could be clinically important in neuro-rehabilitation. For example, the contra-lesional CRT could be a target for neuromodulation therapies in patients with complete injuries of the ipsilesional corticospinal tract and CRT. On the other hand, only three studies were reviewed in this review and one was a case report. Although the CRT has been suggested to be one of the ipsilateral motor pathways from the contra-lesional cerebral cortex to the paretic limbs in stroke, the role of the CRT has not been elucidated clearly. Therefore, further prospective follow-up studies combining functional neuroimaging and transcranial magnetic stimulation for the paretic leg with diffusion tensor tractography will be useful for elucidating the role of the contra-lesional CRT in stroke patients.